Superior antibody immunogenicity of a viral-vectored RH5 blood-stage malaria vaccine in Tanzanian infants as compared to adults - Silk, SE; Kalinga, WF; Mtaka, IM; Lilolime, NS; Mpina, M; Milando, F; Ahmed, S; Diouf, A; Mkwepu, F; Simon, B; Athumani, T; Rashid, M; et al. (Cell Press, 2023)
Background: RH5 is a leading blood-stage candidate antigen for a Plasmodium falciparum vaccine; however, its safety and immunogenicity in malaria-endemic populations are unknown. Methods: A phase 1b, single-center, dose-escalation, age-de-escalation, double-blind, randomized, controlled trial was conducted in Bagamoyo, Tanzania (NCT03435874). Between 12th April and 25th October 2018, 63 healthy adults (18–35 years), young children (1–6 years), and infants (6–11 months) received a priming dose of viral-vectored ChAd63 RH5 or rabies control vaccine. Sixty participants were boosted with modified vaccinia virus Ankara (MVA) RH5 or rabies control vaccine 8 weeks later and completed 6 months of follow-up post priming. Primary outcomes were the number of solicited and unsolicited adverse events post vaccination and the number of serious adverse events over the study period. Secondary outcomes included measures of the anti-RH5 immune response. Findings: Vaccinations were well tolerated, with profiles comparable across groups. No serious adverse events were reported. Vaccination induced RH5-specific cellular and humoral responses. Higher anti-RH5 serum immunoglobulin G (IgG) responses were observed post boost in young children and infants compared to adults. Vaccine-induced antibodies showed growth inhibition activity (GIA) in vitro against P. falciparum blood-stage parasites; their highest levels were observed in infants. Conclusions: The ChAd63-MVA RH5 vaccine shows acceptable safety and reactogenicity and encouraging immunogenicity in children and infants residing in a malaria-endemic area. The levels of functional GIA observed in RH5-vaccinated infants are the highest reported to date following human vaccination. These data support onward clinical development of RH5-based blood-stage vaccines to protect against clinical malaria in young African infants. Funding: Medical Research Council, London, UK.